Sentiment Analysis On Hajj Fund Investment Allocation In Indonesia - Aisyah As-Salafiyah (Halal Tourism and Pilgrimage, 2021)
This study was conducted to determine the sentiments of the Indonesian people, especially sharia economic experts, about their views on the allocation of Hajj financial investment. The method used in this research is a descriptive statistical analysis by conducting sentiment analysis using primary data from expert interviews. The data is then processed using the SentiStrenght application. The results show that the development of Hajj financial investment in Indonesia has a positive sentiment of 28%, a negative sentiment of 12%, and a neutral sentiment of 60%. Bank deposit is an alternative allocation that gets the best sentiment analysis results with a positive sentiment percentage of 50%, neutral 50%, and negative 0%. Meanwhile, the instrument with the lowest sentiment analysis result is Sukuk, with a positive sentiment percentage of 10%, neutral 70%, and negative 20%.